Evaluation of Body Mass Index of 3–10-year-old Children with Adenotonsillar Hypertrophy, who Referred to Khatamolanbia Hospital during 2017–2018 - Khavidaki, Gholam-Ali Dashti; Gharibi, Reza (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Adenotonsillar hypertrophy is a common disorder in the children’s population that can lead to growth disorders. Chronic adenotonsillar hypertrophy can cause a break in the normal growth of children, weight loss, and decreased growth hormone secretion. AIM: The purpose of this study was to evaluate adenotonsillar hypertrophy in the growth rate of children with height, weight, and body mass index (BMI). METHODS: In this descriptive-analytical cross-sectional study, after examining 312, 3–10-year-old children with adenotonsillar hypertrophy, who met the inclusion criteria, growth scales were evaluated and entered into the patient evaluation form. RESULTS: There was a significant relationship between BMI, height, weight, and severity of tonsillar hypertrophy at Brodsky’s scale (P <0.001). Our studies showed well that with increasing severity of adenotonsillar hypertrophy disease, the growth indicators are also decreased in children. CONCLUSION: Adenotonsillar hypertrophy decreases growth indicators in children. There was also a relationship between growth indicators and severity of adenotonsillar hypertrophy in patients.